1999
DOI: 10.1029/1998ja900045
|View full text |Cite
|
Sign up to set email alerts
|

Case studies on the wave propagation and polarization of ELF emissions observed by Freja around the local proton gyrofrequency

Abstract: Abstract. Using a multicomponent measurement of electric and magnetic fields in the ELF range, we investigate the polarization and propagation characteristics of several types of electromagnetic emissions around the local proton gyrofrequency. The data of the loworbiting Freja satellite are examined in the auroral and subauroral regions as well as inside the plasmasphere. We confirm previous results on the properties of the high-latitude hiss with a sharp lower cutoff just below the local proton gyrofrequency.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
60
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 48 publications
(70 citation statements)
references
References 31 publications
10
60
0
Order By: Relevance
“…Other observations, which are consistent with the existence of diverging trajectories, are the measurements of ELF waves by Parrot (1999, 2000) on the lowaltitude satellite FREJA. As the satellite moved through the subauroral region from lower magnetic latitudes (MLAT), it observed that intense downgoing waves first had wave vectors inclined toward the equator.…”
Section: Discussion Observations and General Remarkssupporting
confidence: 57%
“…Other observations, which are consistent with the existence of diverging trajectories, are the measurements of ELF waves by Parrot (1999, 2000) on the lowaltitude satellite FREJA. As the satellite moved through the subauroral region from lower magnetic latitudes (MLAT), it observed that intense downgoing waves first had wave vectors inclined toward the equator.…”
Section: Discussion Observations and General Remarkssupporting
confidence: 57%
“…The direction of k can be obtained by consideringb and one component of the Fourier transform of the electric field,Ẽ 34 [Santolík and Parrot, 1999]. Such an analysis shows that k is parallel to V w 0 (t) and the whistler propagates along ÀB 0 , which is in agreement with how a right-hand polarised wave should propagate.…”
Section: The Normal To the Polarisation Planesupporting
confidence: 63%
“…The determination of the wave vector direction is thus ambiguous. The complete wave vector direction without this ambiguity can be determined using both the magnetic field and the electric field (Lefeuvre et al, 1986-7;Santolík and Parrot, 1999). Having the magnetic field vector data and the two electric components, we use Eq.…”
Section: Analysis Methodsmentioning
confidence: 99%